Binding modes identification through molecular dynamic simulations: A case study with carnosine enantiomers and the Teicoplanin A2‐2‐based chiral stationary phase. Issue 9 (6th April 2020) - Sardella, Roccaldo; Ianni, Federica; Cossignani, Lina; Aldini, Giancarlo; Carotti, Andrea
Abstract: In the present study, an in silico methodology able to define the binding modes adopted by carnosine enantiomers in the setting of the chiral recognition process is described. The inter‐ and intramolecular forces involved in the enantioseparation process with the Teicoplanin A2‐2 chiral selector and carnosine as model compound are successfully identified. This approach fully rationalizes, at a molecular level, the ( S ) < ( R ) enantiomeric elution order obtained under reversed‐phase conditions. Consistent explanations were achieved by managing molecular dynamics results with advanced techniques of data analysis. As a result, the time‐dependent identification of all the interactions simultaneously occurring in the chiral selector‐enantiomeric analyte binding process was obtained. Accordingly, it was found that only ( R )‐carnosine is able to engage a stabilizing charge–charge interaction through its ionized imidazole ring with the carboxylate counter‐part on the chiral selector. Instead, ( S )‐carnosine establishes intramolecular contacts between its ionized functional groups, that limit its conformational freedom and impair the association with the chiral selector unit.